2020
DOI: 10.1111/jonm.13139
|View full text |Cite
|
Sign up to set email alerts
|

Are data on missed nursing care useful for nursing leaders? The RN4CAST@IT cross‐sectional study

Abstract: Rationing within health care, although potentially useful in terms of short-term gains (Scott et al., 2019), is producing reduced safety of care, quality and increased workloads for health care professionals (Harvey et al., 2018). The COVID-19 pandemic emergency has exacerbated the already existing problems caused by time-pressured work environments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
(105 reference statements)
1
11
0
Order By: Relevance
“…Study findings show that MNC occurred in all categories of nursing care. The patterns and reasons of MNC revealed in this study were in line with previous studies in the Czech Republic (Jarošová et al, 2021;Zeleníková et al, 2019Zeleníková et al, , 2020aZeleníková et al, , 2020b and other European studies (Bragadóttir et al, 2017;Palese et al, 2015;Bagnasco et al, 2020) based on the missed care approach and conducted before the COVID-19 pandemic. In line with our results, a Swedish comparative study (von Vogelsang et al, 2021) revealed similar levels and reasons of MNC before and during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Study findings show that MNC occurred in all categories of nursing care. The patterns and reasons of MNC revealed in this study were in line with previous studies in the Czech Republic (Jarošová et al, 2021;Zeleníková et al, 2019Zeleníková et al, , 2020aZeleníková et al, , 2020b and other European studies (Bragadóttir et al, 2017;Palese et al, 2015;Bagnasco et al, 2020) based on the missed care approach and conducted before the COVID-19 pandemic. In line with our results, a Swedish comparative study (von Vogelsang et al, 2021) revealed similar levels and reasons of MNC before and during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…COVID‐19 workplace conditions had a negative impact on nurses’ health (Havaei et al., 2021 ). Therefore, during the time of COVID‐19 crisis, the influence of the NWE on MNC has received a new impetus in nursing research due to exacerbation of pre‐existing workplace conditions contributing to MNC, mainly nurse staffing inadequacies, nurses’ workloads, or time‐pressured work environments (Bagnasco et al., 2020 ). MNC emerges during periods of time scarcity (VanFosson et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study in England reported that most nurses (86%) showed that one or more care activity had been left undone due to lack of time on their last shift. Further, Bagnasco, Catania [16] showed that the frequency of omission of nursing activities ranged between 7% and 50% and oral care was the most frequently missed care activity.…”
Section: Discussionmentioning
confidence: 99%
“…Missed nursing care is an omission error wherein some aspects of required nursing care are partially or totally delayed or unfulfilled [ 8 ]. It occurs in all cultures and countries [ 9 ] and is an important indicator of nursing care quality and patient safety [ 10 ].…”
Section: Introductionmentioning
confidence: 99%